2022
DOI: 10.1097/aci.0000000000000826
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the diagnosis and management of tree nut and seed allergy

Abstract: Purpose of reviewTree nut (TN) and seed allergies are frequent, and their prevalence appears to be on the rise. Allergic reactions associated with these foods are more frequently severe, and these allergies tend to persist into adulthood, consequently affecting quality of life. In this review, we summarize recent advances in diagnostic modalities and management strategies for TN/seed-allergic patients.Recent findingsClinical manifestations of TN and seed allergy range from asymptomatic sensitization to severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…The relatively poor performance of SPT and IgE level results alone in predicting OFC outcome, particularly in the context of equivocal histories of allergy, has prompted attempts to develop novel test modalities. 20 , 21 Novel FA diagnostic approaches include component-resolved diagnostics, 22 , 23 ex vivo allergen activation of allergic cell types, 24 , 25 , 26 , 27 , 28 and epitope mapping. 29 Although these are of great interest and potential, various logistic or biologic aspects of these tests make their widespread adoption difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively poor performance of SPT and IgE level results alone in predicting OFC outcome, particularly in the context of equivocal histories of allergy, has prompted attempts to develop novel test modalities. 20 , 21 Novel FA diagnostic approaches include component-resolved diagnostics, 22 , 23 ex vivo allergen activation of allergic cell types, 24 , 25 , 26 , 27 , 28 and epitope mapping. 29 Although these are of great interest and potential, various logistic or biologic aspects of these tests make their widespread adoption difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, we can now describe sensitization in much greater detail using component-resolved diagnostics (CRD, also known as molecular allergy tests) that measure sIgE response to a large number of allergenic molecules or allergen components (component-specific IgE, c-sIgE). For example, in allergy to peanut [46][47][48] and other foods [49,50], sensitization to some, but not all, allergenic proteins in allergen extracts is important for distinguishing true allergy from asymptomatic sensitization [51]. Consequently, CRD is firmly established in clinical practice in food allergy [52,53], but the data to support a similar approach in the field of asthma are lacking.…”
Section: Component-resolved Diagnostics For Allergic Diseasesmentioning
confidence: 99%
“…Although there are recent reviews on the management and diagnosis of tree nut allergy, 8,9,[41][42][43] this is the first systematic review thoroughly investigating the available information on therapeutic options for the desensitization of patients with IgE-mediated tree nut allergy, other than peanut. Studies addressing the management of tree nut allergy, which did not fulfill the prespecified inclusion criteria of this review, can be found in the Supplementary information.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%